The Relationship of Coronary Artery Disease Severity with the Neutrophil to Lymphocyte Ratio in the Patients Undergoing Coronary Angiography - Huma Naeem Tareen, Muhammad Wali, Sobia Humerah, Muhammad Ahsan Bashir, Syed Mumtaz Anwar Shah, Adeel Tahir (Pakistan Journal of Medical & Health Sciences, 2022)
Background: For identification of the coronary artery diseases the neutrophil to lymphocyte ratio is considered as a well-known marker. Objective: To evaluate the relationship of neutrophil to lymphocyte ratio (NLR) with CAD severity and to determine the reference value of NLR for prediction of the CAD. Study design: It was a cross-sectional study with statistical approach, Peshawar institute of cardiology and Punjab Institute of cardiology Lahore from May 2021 to October 2021. Material and Methods: The 132 patients visited the Peshawar institute of Cardiology and Punjab Institute of cardiology Lahore were included in this research. The patients who had undergone the coronary angiography for angina with ischemic ECG changes were selected. SYNTAX score was used to assess the CAD severity. The high, intermediate and low SYNTAX group was created on the basis of results. The BeneSphera analyzer was used to determine the neutrophil and lymphocyte count. The NLR was calculated. The Pearson’s correlation test, ANOVA and logistic regression analysis was performed for the statistical analysis. Results: Out of the 132 patients were selected, the average age range was between 24 years to 85 years. Among them 67 % of the patients were male and 40 % of patients had a low score of SYNTAX. On the other hand, 33 % of the patients had medium syntax scores. The range of the NLR was between 1.1to9.76 (median 2.54 and mean 3.31 ±1.90). The average standard deviations in low SYNTAX group was 57.12 ±12.018. While it was 61.92±12.23 in intermediate SYNTAX group and 63.01±12.54 high SYNTAX group. The dyslipidemia, diabetes mellitus were more commonly observed in the high SYNTAX group. This group also had low lymphocyte count and high neutrophil count. Conclusion: For the prediction of CAD, the ratio of neutrophils to lymphocytes can be considered. By the calculation of this ratio, it is easy to highlight the correlation between CAD and severity level. Keywords: Coronary angiography, SYNTAX, neutrophil to lymphocyte ratio (NLR), Cardiovascular diseases (CAD).